2004
DOI: 10.1177/154411130401500605
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Enamel Matrix Derivative in the Treatment of Periodontal Defects: a Literature Review and Meta-analysis

Abstract: Background-Periodontal disease results in the loss of the attachment apparatus. In the last three decades, an increasing effort has been placed on seeking procedures and materials to promote the regeneration of this tissue. The aim of this paper is to evaluate the effect of enamel matrix derivative (EMD) during regenerative procedures. In addition, a meta-analysis is presented regarding the clinical results during regeneration with EMD, to gain evidence as to what can be accomplished following treatment of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 122 publications
(263 reference statements)
7
110
1
5
Order By: Relevance
“…After coating the tooth root close to the periodontal defect, the propylene glycol alginate viscosity is reduced under physiological conditions and facilitates EMD release and precipitation [131]. Recent systematic reviews were published on the efficacy of this product in the treatment of periodontal bony defects supporting its use [132][133][134].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…After coating the tooth root close to the periodontal defect, the propylene glycol alginate viscosity is reduced under physiological conditions and facilitates EMD release and precipitation [131]. Recent systematic reviews were published on the efficacy of this product in the treatment of periodontal bony defects supporting its use [132][133][134].…”
Section: Growth Factor Applications For Oral and Periodontal Tissue Ementioning
confidence: 99%
“…The bioactive glass particles were seen in the defect (Specimens stained with Hematoxylin and Eosin, original magnification ×10). 33 Saggital histological section through the calvaria showing defect from 38 the critical size bone grafted with bioactive glass plus enamel matrix derivative after 4 weeks. ( Specimens stained with Hematoxylin and Eosin, original magnification ×5 ).…”
mentioning
confidence: 99%
“…As noted previously, EMD is processed from the unmineralized or partially mineralized enamel matrix of porcine tooth germs, resulting in a bioscaffold for wound healing and tissue regeneration in periodontal, orthopaedic, and dermatologic applications [2,3,45]. The major protein in EMD, amelogenin, is present at the epithelial/mesenchymal transition zone in the tooth germ [6], making it a candidate for modulating osteoblastic differentiation and osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel matrix derivative (EMD) is a decellularized extracellular matrix (ECM) isolated from porcine tooth germs and has been used clinically in a carrier as Emdogain (Institut Straumann AG, Basel, Switzerland) to promote periodontal tissue regeneration, including periodontal ligament, alveolar bone, and cementum [1][2][3]. It has been suggested that EMD induces periodontal tissue regeneration by mimicking events in normal periodontal tissue development [4].…”
Section: Introductionmentioning
confidence: 99%